THE INFLUENCE OF SOCIAL INTERACTION ON IMPULSIVE BUYING THROUGH HEDONIC AND UTILITARIAN VALUES IN LIVE STREAMING SHOPPING - Lady; Sherlen Sherlen; Fendy Cuandra (Universitas Sarjanawiyata Tamansiswa, 2026)
This study investigates how social interaction affects impulsive buying urges in live streaming shopping, with hedonic and utilitarian values serving as mediating variables. The forms of social interaction analyzed include parasocial interaction with streamers and co-viewers, as well as local and social presence. A quantitative research design was applied using a survey method involving 350 active live streaming shoppers in Batam City. Data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study show that every form of social interaction analyzed, including interaction with streamers, interaction with co-viewers, local presence, and social presence of viewers, significantly strengthens both utilitarian value and hedonic value perceived by consumers. Furthermore, utilitarian value and hedonic value each demonstrate a significant negative effect on the urge to buy impulsively, meaning that when consumers perceive stronger functional benefits or pleasurable experiences, their tendency to make sudden and spontaneous purchases actually becomes lower during live streaming shopping. In addition, gender is proven to significantly influence the strength of these relationships, while prior purchase experience does not show a meaningful moderating effect.